Ex utero intrapartum treatment (EXIT) procedure: Indications and procedural considerations - Melissa Silva (Journal of Perioperative Nursing)
Problem identification: Ex Utero Intrapartum Treatment (EXIT) has become the optimal delivery strategy in fetuses with airway compromise; however, it remains an extremely rare procedure. This review aims to provide perioperative nurses with an overview of EXIT procedure to enable them to be an effective member of the multidisciplinary team.